2012
DOI: 10.3390/medicina48100080
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of Lung Sirtuin Expression in Smokers With and Without Chronic Obstructive Pulmonary Disease

Abstract: Background and Objective. Chronic obstructive pulmonary disease is characterized by persistent and modified inflammatory responses in lung. Human sirtuin, an antiaging and antiinflammatory protein, is a metabolic NAD(+)-dependent protein/histone deacetylase that regulates proinflammatory mediators by deacetylating histone and nonhistone proteins. The aim of our study was to compare the expression of sirtuin in large and small airways in nonsmokers, asymptomatic smokers, and smokers with chronic obstructive pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…It has been observed that in the large airways of COPD patients and smokers, Sirt1 expression was lower than in healthy people. On the contrary, in the small airways of COPD patients, a significant reduction of Sirt1 levels was found compared to the lung of smokers and healthy controls [89]. In addition, the exposure to chronic cigarette smoke, in COPD patients, enhanced matrix metallo-proteinases 2, 9 and 12 and this phenomenon was associated with low Sirt1 level too [90].…”
Section: The Involvement Of Sirtuins In Other Pathophysiological Condmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been observed that in the large airways of COPD patients and smokers, Sirt1 expression was lower than in healthy people. On the contrary, in the small airways of COPD patients, a significant reduction of Sirt1 levels was found compared to the lung of smokers and healthy controls [89]. In addition, the exposure to chronic cigarette smoke, in COPD patients, enhanced matrix metallo-proteinases 2, 9 and 12 and this phenomenon was associated with low Sirt1 level too [90].…”
Section: The Involvement Of Sirtuins In Other Pathophysiological Condmentioning
confidence: 90%
“…Whether Sirt1 plays a role in this context remains to be determined. However, it must be noted, that different results have been obtained studying cells coming from large and small airways such as macrophages, lymphocytes and endothelial cells [89]. In a study, three groups of patients were compared: COPD smoker, smokers without COPD and healthy no-smokers.…”
Section: The Involvement Of Sirtuins In Other Pathophysiological Condmentioning
confidence: 99%
“…Whether Sirt1 plays a central role in this context remains to be determined. However, it must be noted that different results have been obtained studying cells coming from large and small airways such as macrophages, lymphocytes and endothelial cells [90]. In a study, the following groups of patients were compared: COPD smoker, smokers without COPD and healthy nonsmokers.…”
Section: The Involvement Of Sirtuins In Other Pathophysiological Condmentioning
confidence: 99%
“…Using immunohistochemistry and western blotting, sirtuins were shown to be highly suppressed in large and small airways in human COPD, in which smoking led to suppression mainly in the large airways [38]. Epigenetic factors play a role in development of fibrosis [39].…”
Section: Sirtuins In Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%